Ferritin 2 domain-containing protein found in lacquer tree (Toxicodendron vernicifluum) sap has negative effects on laccase and peroxidase reactions. Issue 6 (3rd June 2017) - Kitajima, Sakihito; Imamura, Taiki; Iibushi, Junpei; Ikenaga, Makoto; Tachibana, Yoichi; Andoh, Nobuyuki; Oyabu, Hiroshi; Hirooka, Kiyoo; Shiina, Takashi; Ishizaki, Yoko
Abstract: Lacquer tree sap, a raw material of traditional paints in East Asia, is hardened through laccase-catalyzed oxidation and the following polymerization of phenolic compound urushiol. In the sap's water-insoluble fraction, we found two plantacyanins and a ferritin 2 domain-containing protein (TvFe2D, a homolog of Arabidopsis AT1G47980 and AT3G62730). The recombinant TvFe2D protein suppressed the accumulation of laccase-catalyzed oxidation products of a model substrate syringaldazine without decreasing oxygen consumption, the second substrate of laccase. The suppression was also observed when another substrate guaiacol or another oxidizing enzyme peroxidase was used. The functional domain of the suppression was the C-terminal half, downstream of the ferritin 2 domain. The results suggest that this protein may be involved in regulating the sap polymerization/hardening. We also discuss the possibility that homologous proteins of TvFe2D in other plants might be involved in the laccase- or peroxidase-mediated polymerization of phenolic compounds, such as lignin and flavonoids. Graphical abstract: : Sap exuded from the wound site of lacquer tree. The ferritin 2 domain protein in it is a novel candidate regulating urushiol polymerization/hardening.